Rapid BAL Variability: Re-Emerging Absorption - Erakuman, Damla; Filiz Ak, Nurten (Frontiers in Astronomy and Space Sciences, 2017)
We study BAL variations of SDSS~J141955.28+522741.4 utilizing 32 epochs of spectroscopic observations from SDSS. We identify three individual BAL troughs for CIV and one BAL trough for SiIV. The deepest CIV BAL trough show significant EW variations in timescales of a few ten hours. The fast component of the deepest CIV BAL present disappearance and re-emergence preserving its initial velocity range and profile. All identified BAL roughs show coordinated variations supporting that the possible mechanism behind these BAL variations likely to be ionization level changes of absorbing gas.